Aaerobic Capacity of Health Care Students at Riga Stradinš University - Arnis, Voldemārs; Vīnberga, Indra; Upeniece, Irēna; Šmite, Daina; Hoferte, Maruta; Gauruča, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Aerobic capacity (AC) is one of health indicators that characterise the functional status of heart, blood vessels, respiratory and other bodily systems. Aerobic capacity depends on several factors: the health conditions, gender, age and the level of physical activities. Students spend many hours in a sitting position in lectures, libraries, when preparing homework, as well as when watching the TV and sitting by the computer. As a result students’ work abilities decrease and the health conditions deteriorate. Health care specialists should be physically active, not only for the sake of their well-being and health conditions, but also they should to be able to motivate their clients to have an active lifestyle.Objective of the research. The objective of the research is to explore aerobic capacity of healthcare students and analyse it within the context of the respective age group population. Aerobic capacity was determined for 730 students (517 women and 213 men in the age group from18 to 30 years) by applying the veloergometry test of the World Health Organisation (WHO) and using veloergometersMonarkErgomedik 839E. Pursuant to the WHO test results during the studies aerobic capacity indicators deteriorated for the majority of students.